Engaging Health System Decision-makers in Supporting Comprehensive Chronic Pain Management in Provincial and Territorial Healthcare Systems in Canada - McMaster Health Forum (My University, 2011)
Two-page overview of what was learned from a stakeholder dialogue on the topic of engaging health system decision-makers in supporting comprehensive chronic pain management in provincial and territorial healthcare systems in Canada.
Keywords: health system; decision-makers; chronic pain; provincial; territorial; healthcare; Canada